Konsep Kebikan Moneter dalam Perspektif Hukum Ekonomi Syariah - Abdianti, Dini; Restu, Anisa; Al ayyubi, Sholahuddin (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2023)
Monetary policy in Islamic economic law is a key branch of economic studies that focuses on understanding the nature, functions, and impacts of monetary actions on the economic activities of a nation. In Islamic economics, monetary policy is not solely concerned with the supply and demand of money but also integrates principles of justice, equity, and brotherhood, aiming for equality and the fair distribution of wealth and income. This article adopts a qualitative research approach, with data analysis conducted through descriptive analysis. Descriptive analysis is used to present the research findings clearly, based on the evidence gathered. The findings indicate that monetary policy plays a vital role in maintaining economic stability by ensuring a balanced distribution of money within the economy. When the circulating money supply is not proportional to the amount of goods and services available, it can disrupt economic stability. This study highlights that in Islamic economic law, the balance between money supply and the production of goods and services is crucial for preventing economic instability and ensuring equitable wealth distribution.